The Regional Representative Council (DPD RI) and Checks and Balances in Indonesia's Legislative Process - Cipto Handoyo, Benediktus Hestu (Magister Hukum Universitas Semarang, 2024)
This study aims to analyze the function of the House of Regional Representatives of the Republic of Indonesia (DPD RI) in the legislative process and the checks and balances mechanism within Indonesia's constitutional system. The background of this research stems from the limited authority of DPD RI in the legislative process, especially when compared to the House of Representatives (DPR RI), despite its vital role as a regional representation body advocating for regional interests in law-making. The urgency of this writing lies in addressing the imbalance of power between the executive and the legislature, as well as between the central government and the regions. Using a normative legal research method, this article examines the role of DPD RI in the discussion of bills, its interactions with DPR RI, and its contributions to maintaining the checks and balances system. The findings indicate that the DPD RI faces significant challenges in influencing the legislative process, although opportunities exist for strengthening its role. The study concludes that legislative reforms and capacity building for DPD RI are crucial to enhance the effectiveness of the checks and balances mechanism, thereby strengthening Indonesia's democratic system. The novelty of this research lies in its emphasis on practical strategies for empowering DPD RI within the national legislative framework.